Exploring the complexity of participation. Issue 4 (2nd October 2021) - Mosleh, Wafa Said; Larsen, Henry
ABSTRACT: This research aims to re-articulate the concept of participation in design research by adopting a relational, temporal, and process-oriented perspective. In the paper, we draw on recent theory where human interaction is understood as complex responsive processes of relating. Thus, participation is seen as people taking part in creating social objects that emerge in the complex social processes of everyday organisational life. This perspective challenges conceptions of participation as normative as well as the tendency to make methods of participation generalisable and replicable. Based on an organisational case in which multiple stakeholders are involved in collaborative design processes, we describe how social dynamics and issues of power, enable and constrain participation and argue that participation cannot, strictly, be accounted for on the foundation of designed temporary workshop spaces, methods, and tools for engagement or the facilitation of the researcher or designer. On that basis, we will introduce a concept which argues that participation is how people engage the temporal emergence of daily interactions and ongoing conversations that unfold in complex processes of relating, influencing action, interaction, identity, and meaning.